MULTIMODALITY IN EXTENSIVE LISTENING: A CASE STUDY OF INDONESIAN EFL STUDENTS - Fitri, Sherly Annisa; Gunawan, Muhammad Handi; Nurlaelawati, Iyen (English Review: Journal of English Education, 2025)
Listening comprehension is a crucial component of language learning, with extensive listening (EL) recognized as an eﬀective strategy for language learners. However, the majority of listening resources in classrooms are often limited to audio-only formats, presenting challenges for students. This study explores the potential of multimodality, defined as the combined utilization of various communication modalities, in enhancing the EL experience. Despite the increasing research on multimodality in language education, a notable gap exists in understanding how students perceive the combined use of multiple modes, especially in EL classes. This research employed a case study design involving EFL students in a public university in Indonesia. The study utilized course reflections which served as open-ended questionnaires, and semi-structured interviews to gather insights into students’ perceptions and challenges related to multimodal materials in EL instruction. The findings reveal that students generally find multimodality beneficial in understanding the context of EL materials. However, challenges arise when there are too many modes, leading to distractions and reduced eﬀectiveness. This research contributes to addressing the research gap and emphasizes the importance of examining students’ perceptions and challenges in the context of EL classrooms employing multimodality.